Respuestas

  • Usuario de Brainly
2013-05-02T19:55:56+02:00

tenemos

 

\frac{tan(x)+cos(x)}{sen(x)}=sec(x)+cot(x)\\ \\ \frac{\frac{sen(x)}{cos(x)}+cos(x)}{sen(x)}=sec(x)+cot(x)\\ \\ \frac{\frac{sen(x)}{cos(x)}}{sen(x)}+\frac{cos(x)}{sen(x)}=sec(x)+cot(x)\\ \\ \frac{1}{cos(x)}+\frac{cos(x)}{sen(x)}=sec(x)+cot(x)

 

sabemos que:

 

\frac{1}{cos(x)}=sec(x)\\ \\ \\ \frac{cos(x)}{sen(x)}=cot(x)

 

 

por lo que...

 

\frac{1}{cos(x)}+\frac{cos(x)}{sen(x)}=sec(x)+cot(x)\\ \\ sec(x)+cot(x)=sec(x)+cot(x)

 

 

saludos.

 

2013-05-02T19:57:11+02:00

tan x = sen x / cos x

sec x = 1/cos x

cot x = cos x / sen x 

[(sen x/cosx) + cos x] / sen x = 1/cos x + cos x / sen x

(sen x + cos 2 x)/ sen cos x = (sen x + cos 2 x) / sen x cos x

 

Los dos miembor sosn iguales, ya está demostrada la identidad